Morphology and deformational history of Tellus Regio, Venus: Evidence for assembly and collision. (May 2018) - Gilmore, M.S.; Head, J.W.
Abstract: Tessera terrain is the oldest stratigraphic unit on Venus, but its origin and evolution are inadequately understood. Here we have performed detailed mapping of Tellus Regio, the third largest tessera plateau on Venus. Tellus Regio is shown to have distinct marginal and interior facies. The east and west margins of Tellus rise up to 2 km above the interior and include ridges and troughs ∼5–20 km across, oriented parallel to the present plains-tessera boundary. Structures characteristic of the interior of Tellus are found within the eastern and western margins and are deformed by the margin-parallel ridges indicating their presence during the time of the formation of the current margins. These relationships suggest that the margins formed by the application of external horizontal compressional stresses at the edges of an already-existing tessera interior. Structural and stratigraphic relationships in southwest Tellus show the assembly of three structurally distinct tessera regions and intervening plains that are consistent with the collision of the southwest margin into the plateau interior. This requires that tessera terrain was formed regionally and collected into the present day Tellus plateau. The latest stages of activity in Tellus include volcanism and pervasive, distributed, 1–2 km wide graben, which may have been formed due to large-scale gravitational relaxation of the plateau topography. A large intratessera plains unit may have formed via crustal delamination. The collisional oroclinal deformation of the margins are most consistent with models that invoke mantle downwelling for the origin of Tellus Regio and other tessera plateaus with similar structural relationships. Highlights: Tellus Regio Tessera has undergone multiple episodes of compressional followed by extensional deformation. The tessera margins postdate and deform the interior. SW Tellus shows evidence for the assembly of several individual tessera provinces.